Dynamics of Bangladesh-India relations : dialogue of young journalists across the border - Bangladesh-India Dialogue for Young Journalists 2004 : Bangladesh Enterprise Institute); Sobhan, Farooq; Bangladesh Enterprise Institute; Bangladesh-India Dialogue for Young Journalists 2004 November 30-December 1st : Bangladesh Enterprise Institute) (Dhaka : The University Press, 2005)
Contributed articles on Bangladesh relations with India presented at two Bangladesh-India Dialogue for Young Journalists on September 7-8 and November 30th-December 1st 2004.
"Bangladesh Enterprise Institute."
Includes bibliographical references.
Keywords: Bangladesh -- Relations -- India -- Congresses; India -- Relations -- Bangladesh -- Congresses